2018
DOI: 10.4103/psychiatry.indianjpsychiatry_194_17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moderate learning style–teaching mode mismatch on academic performance among 2nd year medical students in Pakistan

Abstract: Introduction:The vagueness surrounding “learning style–teaching mode mismatch” makes its effects uncertain. This study tried to tackle that controversy by comparing and assessing the effect of different learning styles on performance in physiology examination when teaching mode was somewhat different than learning preferences of the 2nd year medical students.Methods:A total of 102 2nd year medical students participated in this study. Honey and Mumford learning style questionnaire was used to categorize the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
1
3
0
1
Order By: Relevance
“…However, our results failed to support hypothesis 2, which was that students who were activists or pragmatists would have high game performance scores. This finding is in line with other studies, which have shown a lack of a direct relationship between learning experience and academic performance in medical students [35][36][37]. It is possible that learning style can engage students in learning in serious games; however, it might not be a predictor of academic success.…”
Section: Principal Findingssupporting
confidence: 91%
“…However, our results failed to support hypothesis 2, which was that students who were activists or pragmatists would have high game performance scores. This finding is in line with other studies, which have shown a lack of a direct relationship between learning experience and academic performance in medical students [35][36][37]. It is possible that learning style can engage students in learning in serious games; however, it might not be a predictor of academic success.…”
Section: Principal Findingssupporting
confidence: 91%
“…çalışmalarında son sınıftaki değiştiren öğrenme stiline sahip kadın öğrencilerin uzmanlıkta daha çok dahili bir dal tercih ettiğini; özümseyen gruptaki erkek öğrencilerin ise ağırlıklı olarak cerrahi bir dal seçtiğini gözlemledi (24). Literatürde öğrenme stillerinin farklı ölçekler ile değerlendirildiği başka çalışmalar öğrenme stilinin ve cinsiyet arasındaki ilişkiden bahsedilmektedir (3,6,28). Ancak biz çalışmamızda Cortes ve ark.…”
Section: Hematoloji Uzmanlarının öğRenme Stilleriunclassified
“…By addressing students' specific learning styles, teachers can solve students' problems and prepare students for real-life skills. Further, it has been argued that students do not learn if the teaching style does not match with the students' learning style (Hamza, Inam-Ul-Haq, Nadir, & Mehmood, 2018). Therefore, with a suitable teaching style, teachers can get students engaged in the learning process.…”
Section: Importance Of Understanding Learning Stylesmentioning
confidence: 99%